Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Melati Rsj Prof. Hb. Saanin Padang - Meissy Kurnia; Vivi Yuderna; Ramaita .; Dwi Happy Anggia Sari (CV. ITTC INDONESIA, 2026)
Hallucinations are sensory perception disorders involving subjective experiences of unreal stimuli through one or more of the five senses, including sight, smell, touch, or taste, and hearing. Based on the data obtained, being diagnosed with hallucinations is the most common diagnosis at Prof. HB. Saanin Mental Hospital Padang in the last 3 years (2023-2025), namely 17,591 patients. The purpose of this study is to apply psychiatric nursing care to patients with hallucinations at Wisma Melati Prof. HB. Saanin Mental Hospital Padang. The research method is a descriptive case study conducted over 6 meeting days (February 9-14, 2026). Results: the client was able to control hallucinations by implementing SP 1-4 for hallucinations and SP 1-4 for self-care deficit. Conclusion: the client was able to independently control hallucinations using the methods taught by the nurse. This study is expected to serve as a reference for optimizing psychiatric nursing care.